Enhancing the saturable absorption and carrier dynamics of graphene with plasmonic nanowires. Issue 10 (29th June 2015) - Wang, Hancong; Miao, Lili; Jiang, Yaqin; Lu, Shunbin; Li, Zhipeng; Li, Pan; Zhao, Chujun; Zhang, Han; Wen, Shuangchun
<x xml:space="preserve">Abstract</x> We experimentally investigated the nonlinear optical response in few‐layered graphene/silver nanowires (G/NWs) hybrid films that consist of two‐dimensional graphene and network of one‐dimensional silver nanowires, and found an enhanced third‐order optical nonlinearity based on the open‐aperture femtosecond Z‐scan measurement. The enhancement of the optical nonlinearity is attributed to interfacial nanowires network on graphene for large local field enhancement and exciton–plasmon–photon conversion channel. In addition, accelerated carrier relaxation times in G/NWs are also observed by optical pump–probe spectroscopy, in which nanowires might supply an additional relaxation channel for graphene. The nanowire‐induced defects and the increase of either electrons or holes induced by charge transfer may also contribute to the ultrafast dynamics in G/NWs. Our findings provide a new avenue of modulating the nonlinear optical response of graphene‐related materials, and further suggest that G/NWs could be developed as nonlinear optical material in novel tunable laser photonics devices, such as laser mode locker, Q switcher, etc.